2019
DOI: 10.1089/ars.2017.7350
|View full text |Cite
|
Sign up to set email alerts
|

Proline Metabolism in Cell Regulation and Cancer Biology: Recent Advances and Hypotheses

Abstract: The proline metabolic axis can serve as a scaffold on which a variety of regulatory mechanisms are integrated. Once understood as a central mechanism in cancer metabolism, proline metabolism may be a good target for adjunctive cancer therapy.-Antioxid. Redox Signal. 00, 000-000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
209
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(213 citation statements)
references
References 105 publications
(223 reference statements)
4
209
0
Order By: Relevance
“…Thus, when cells are proliferating or not, they can store or not their metabolic substrates in the ECM 26,29 . However, when collagen is degrading, Proline is converted in amino acids 42 . This process is what has been highlighted by the RS, with bands assigned to Proline and collagen progressively less intense from EC to CS G1 and Cs G2, and the intensification of bands assigned to Tyr and Trp, as well as to the Phe for the CS G3.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when cells are proliferating or not, they can store or not their metabolic substrates in the ECM 26,29 . However, when collagen is degrading, Proline is converted in amino acids 42 . This process is what has been highlighted by the RS, with bands assigned to Proline and collagen progressively less intense from EC to CS G1 and Cs G2, and the intensification of bands assigned to Tyr and Trp, as well as to the Phe for the CS G3.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of proline could promote cell proliferation, energy production and resistance to oxidative stress (act as an antioxidant) [16][17][18][19]. L-valine is an essential and important functional amino acid involved in many growth and metabolic processes, and is also a glucogenic amino acid for biosynthesizing macromolecules (e.g., proteins and lipids), which are vital to the growth of cancer cell [20]. The accumulation of amino acids could ascribe to the proliferation by cancer cells, suggesting cancer transformation is linked with adaptive increases in protein synthesis [21].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ROS can participate in the regulation of different signaling pathways and epigenetic mechanisms. In cancer, it has been shown that enzymes involved in proline biosynthesis are dysregulated, promoting an increase in proline, which impacts upon exacerbated tumor growth [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%